Cancer of the cervix uteri: magnetic resonance and clinical factors of prognosis - A. A. Proshin; T. P. Berezovskaya; L. I. Krikunova; Z. N. Shavladze (Опухоли женской репродуктивной системы, 2014)
Based on their observations, the authors have made univariate and multivariate analyses of the prognostic importance of a number of magnetic resonance and clinical factors in cancer of the cervix uteri.